Agenda Media Detik.com Tentang Film Dirty Vote - Rasyid, Nur Aini; Herawati, Maimon; Sirait, Rinda Aunillah (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2025)
The media has a significant role in shaping public opinion through the attention it gives to certain issues. The same is true in a political context such as the 2024 election, where the Dirty Vote movie has drawn controversy for revealing the 2024 Election fraud scheme but aired during the quiet period. This study aims to analyze Detik.com's media agenda in the coverage of the film ‘Dirty Vote’ during the period 11-14 February 2024, focusing on the three dimensions of the media agenda according to Manheim (1987): visibility, audience salience, and valence. The method used was descriptive quantitative content analysis of 43 news articles from Detik.com. The results show that Detik.com accentuates the issue of power elite response in the ‘Election Rigging Response’ issue category (27.9%) and political conflict in the ‘Controversial Film’ issue category (16.3%) in the visibility dimension with the dominance of news values ‘Power Elite’ (32.6%) and ‘Conflict’ (23.3%) as indicators of the audience salience dimension. Meanwhile, in the valence dimension, the tone of the news was dominated by a neutral tone (48.8%), more sources were quoted from Prabowo-Gibran supporters (20.9%) and the government (20.9%). The contribution of this research lies in strengthening understanding of the dynamics of online media agendas in the context of controversial issue coverage, as well as practical recommendations for the media to improve the balance and depth of analysis. Keywords: Media Agenda, Detik.com, Dirty Vote, Content Analysis, Indonesia General Election 2024